Análise de aspectos experienciais da participação de adultos com deficiência motora no Brasil através da aplicação do IPA-Br4 - Ana Amélia Moraes Antunes (2023)
ANTUNES, Ana Amélia Moraes. Analysis of experiential aspects of the participation of adults with motor disabilities in Brazil through the application of the IPA-Br4. 2023. 103 f. Thesis (Doctorate in Rehabilitation Sciences) – School of Physical Education, Physiotherapy and Occupational Therapy of the Federal University of Minas Gerais. Belo Horizonte, 2023. Introduction: Consistent definitions and operationalizations of participation are essential for proper assessment and the development of effective rehabilitation services. Subjective aspects of participation must be measured to guide interventions and research. Methods: This thesis is composed of three studies: a systematic literature review to analyze instruments that assess experiential aspects of participation; investigation of the measurement properties of the instrument defined from the review, Impact of Participation and Autonomy-Br4 (IPA-Br4) for adults with motor disabilities; and the investigation of participation levels and personal factors and health condition, in individuals monitored in a rehabilitation service. Results: In the review, 10 instruments were identified. Evidences of content validity and internal structure (structural validity and internal consistency) were analyzed, according to the criteria of the Consensus-based Standards for the Selection of Health Measurement Instruments. Only three instruments, still without Brazilian versions, had good coverage of subjective aspects of participation, of which one presented high-quality evidence of structural validity. Between the two instruments with Brazilian versions, the review pointed to high-quality evidence that the Participation Scale is not unidimensional, so its score cannot be considered an adequate indicator of the level of participation. The Impact on Participation and Autonomy (IPA) scale has good coverage of subjective aspects of participation in two of its five domains (Social Life and Relationships, Autonomy Outdoors) while the others (Autonomy Indoors, Family Function and Family Function) relate to the activity. The review indicated the need for further investigation into the internal structure of the IPA. In the second study, the internal structure (n =130) and the test-retest reliability (n =30) of the Brazilian version (IPA-Br4, which does not contain the Work and Education domain) were investigated. Good rates of reliability, structural validity and internal consistency were demonstrated for a digital version of the scale. In the third study, self-reported activity and participation levels (n=160), measured by the IPA, were analyzed and the relationships between domain scores and age, sex, impairment motor, continence, fatigue, type and duration of injury. In general, the results indicated reasonable to good autonomy for all domains. Fatigue had a negative effect on 01 domain. Conclusions: The digital version of the IPA-Br4 has test-retest reliability and adequate internal structure in adults with motor disabilities. A sample of this population, monitored in a rehabilitation service, reports autonomy for reasonable to good participation. In this sample, health condition, age and sex factors did not interfere with participation.